2009
DOI: 10.2174/1876400200902010027
|View full text |Cite
|
Sign up to set email alerts
|

Developing Sustainable Waste Management Practice: Application of Q Methodology to Construct New Strategy Component in Limbe - Cameroon

Abstract: The most important motivation for developing new waste management strategy and policy relates to the waste management behavior of individuals. Education led campaigns and capacity building programmes involving third sector organizations in waste management are gaining momentum, in some major cities in Cameroon. There is however, a need to use research methodologies to investigate elements of waste management behavior to understand how to change behaviour permanently. Although the use of quantitative research m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…Such conflicts however could be avoided if urban councils formalise all waste operation activities and set clear rules of operation whereby zones of operation and all other requirements are strictly adhered to. This is only possible for waste pickers if organised in formal groups that can be legally registered, monitored and supervised as reported in studies by Mbeng et al, (2009) …”
Section: Final Disposal Of Wastementioning
confidence: 99%
See 3 more Smart Citations
“…Such conflicts however could be avoided if urban councils formalise all waste operation activities and set clear rules of operation whereby zones of operation and all other requirements are strictly adhered to. This is only possible for waste pickers if organised in formal groups that can be legally registered, monitored and supervised as reported in studies by Mbeng et al, (2009) …”
Section: Final Disposal Of Wastementioning
confidence: 99%
“…The main problems of the composting project are sorting which is not done at source but on delivery of wastes, mixed wastes of all categories increasing health risk to workers and lack of market for the compost. Some authors (Matete & Trois, 2008;Mbeng et al, 2009;Mbuligwe & Kasenga, 2004;Rotich et al, 2006;Wang et al, 2008) have identified recycling, composting and biogas production as feasible options with social, economic and environmental benefits by reducing amounts of waste disposed, saving the environment and generating income for communities the lack of municipal integration and support leaves composting, which is technically viable, to be strongly vulnerable to external factors (Oberlin & Sza´nto´, 2011).In East Africa these innovative methods for waste management remain un-researched denying interested individuals among the urban communities information on such projects.…”
Section: Solid Waste Management Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…The subjects were selected by purposive sampling from three private waste management companies in Sagamu, southwest of Nigeria, in line with previous studies. [19282930] Both categories of waste workers function under private facilities with informal operations, work eight hours daily and for six days every week. The TUs received informal training before commencement of work, whereas the CPs had no such training.…”
Section: Methodsmentioning
confidence: 99%